Ex Vivo Molecular Rejuvenation Improves the Therapeutic Activity of Senescent Human Cardiac Stem Cells in a Mouse Model of Myocardial Infarction. (September 2014) - Avolio, Elisa; Gianfranceschi, Giuseppe; Cesselli, Daniela; Caragnano, Angela; Athanasakis, Emmanouil; Katare, Rajesh; Meloni, Marco; Palma, Anita; Barchiesi, Arianna; Vascotto, Carlo; Toffoletto, Barbara; Mazzega, Elisa; et al.
Abstract Cardiac stem cells (CSC) from explanted decompensated hearts (E‐CSC) are, with respect to those obtained from healthy donors (D‐CSC), senescent and functionally impaired. We aimed to identify alterations in signaling pathways that are associated with CSC senescence. Additionally, we investigated if pharmacological modulation of altered pathways can reduce CSC senescence in vitro and enhance their reparative ability in vivo. Measurement of secreted factors showed that E‐CSC release larger amounts of proinflammatory cytokine IL1β compared with D‐CSC. Using blocking antibodies, we verified that IL1β hampers the paracrine protective action of E‐CSC on cardiomyocyte viability. IL1β acts intracranially inducing IKKβ signaling, a mechanism that via nuclear factor‐κB upregulates the expression of IL1β itself. Moreover, E‐CSC show reduced levels of AMP protein kinase (AMPK) activating phosphorylation. This latter event, together with enhanced IKKβ signaling, increases TORC1 activity, thereby impairing the autophagic flux and inhibiting the phosphorylation of Akt and cAMP response element‐binding protein. The combined use of rapamycin and resveratrol enhanced AMPK, thereby restoring downstream signaling and reducing IL1β secretion. These molecular corrections reduced E‐CSC senescence, re‐establishing their protective activity on cardiomyocytes. Moreover ex vivo treatment with rapamycin and resveratrol improved E‐CSC capacity to induce cardiac repair upon injection in the mouse infarcted heart, leading to reduced cardiomyocyte senescence and apoptosis and increased abundance of endogenous c‐Kit+ CSC in the peri‐infarct area. Molecular rejuvenation of patient‐derived CSC by short pharmacologic conditioning boosts their in vivo reparative abilities. This approach might prove useful for refinement of CSC‐based therapies. Stem Cells2014;32:2373–2385